Research in dentistry: Question, search and studies design. - Pedro Aravena (Universidad de Concepción., 2012)
Evidence-based dentistry (EBD) concept has caused great impact and interest in the field of dentistry. For its development is important to use research protocols and study designs according to the research problem. The aim of this review is to present basic aspects for the start of a quantitative research in dentistry.It presents the topics necessary to transform a research problem to a question with clinical approach. Then, concepts about finding relevant scientific articles in the electronic databases available on the Internet. It also presents observational and experimental research designs, their classification and topics for your choice. These elements represents simple and clear recommendations for research in dentistry.